BRIDGING POLICY AND PRACTICE: READINESS TO INTEGRATE ASSESSMENT CENTER OUTPUTS INTO TALENT MANAGEMENT IN THE NTT PROVINCIAL GOVERNMENT - Aman, Lusius; Kapa, Johanes Baptista Avodius; Trihastuti, Santa Anna; Pau, Theresia Mariyati Pranatalia (Kebijakan : Jurnal Ilmu Administrasi, 2026)
This study examines the organizational readiness of the NTT Provincial Government to integrate Assessment Center (AC) outputs into its Talent Management (TM) system. Although regulations mandate the use of competency assessment in talent decisions, AC results remain weakly embedded in practice. Using a mixed-method approach—document analysis, a structured questionnaire (n = 48), and a Focus Group Discussion (n = 20)—the study assesses readiness across institutional, technical, human resource, and cultural dimensions. The findings indicate moderate overall organizational readiness (mean = 3.22). Technical readiness (3.94) and human resource capability (3.95) are relatively strong, reflecting adequate infrastructure and personnel professionalism. However, institutional readiness (3.15) and cultural readiness (2.58) remain weak, characterized by the absence of operational SOPs, limited system integration, uneven managerial interpretive capacity, and persistent non-merit staffing practices. The study identifies a condition of asymmetric organizational readiness, in which strong technical and individual capacities coexist with weak institutional and cultural foundations. This imbalance produces a readiness paradox, resulting in symbolic rather than substantive AC–TM integration. The findings extend organizational readiness theory and offer policy-relevant insights for strengthening evidence-based talent management in decentralized public administrations.